Aging Does Not Enhance Social Contagion Effect - Carnero-Sierra, Susana; Menor, Julio (Frontiers in Psychology, 2021)
Studies on the social contagion of memory show that it is possible to create false memories from the wrong responses from other people without requiring their physical presence. The current study examined age differences between false memories via the modified social contagion paradigm. Twenty older and twenty younger adults were shown six household scenes and were exposed to the erroneous memory reports of an implied confederate who was not physically present. The presentation time of the scenes and the typicality of the contagion items were manipulated. The participants watched each scene individually and then took turns giving their recall responses with the responses belonging to a fictional participant provided by written cards. The results in a final individual recall test indicated a significant contagion effect in both groups of participants. Additionally, an effect of the typicality of the contagion items was observed, such that the more typical items produced more contagion than the less typical items. In relation to true recall, the older adults remembered significantly fewer items from the scenes than the younger ones and obtained a lower score in the word list subtest of the Weschler Memory Scale. Although the older group had an episodic memory deficit, they were not more susceptible to being affected by the wrong responses of other people than younger group.